2022
DOI: 10.1186/s12903-022-02277-0
|View full text |Cite
|
Sign up to set email alerts
|

Salivary expression of lncRNA DQ786243 and IL-17 in oral lichen planus: case–control study

Abstract: Background A growing number of studies has investigated IL-17 in OLP. However, its exact role and interactions are not fully determined. In addition, the literature investigating its salivary expression is limited. The scarcity in the literature studying lncRNAs was noticed, particularly with regards to correlating them with cytokines in OLP. In the current study, the salivary expression of lncRNA DQ786243 and IL-17 was assessed among different forms of OLP. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…88 Several studies showed significant upregulation of IL-17 in tissue, serum, and saliva samples of OLP patients compared with healthy controls. 2,9,11,15,16,23,32,44,78,79,82,[88][89][90][91] Considering T-cell-mediated immune response in pathogenesis of OLP, presence of IL-17 and its regulatory role in OLP is not surprising. It participates in the pathogenesis of OLP through the following mechanisms: (I) reinforcement of T lymphocyte reactions and production of inflammatory mediators such as IL-6, IL-8, and IL-1B, 15,78 (II) regulation of production of matrix metalloproteinase-9 (that breaks type IV collagen leading to impairment of the basement membrane and apoptosis of keratinocytes), 92,93 (III) reduction in diversity of oral bacteria (providing an opportunity for opportunistic pathogens to stimulate the innate and acquired immune system and lead to disease flare-up), 88 (IV) and increased hypersensitivity reactions (through degranulation of mast cells).89 Th17 cells are imperative to coordinate the immune responses elicited by extracellular bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…88 Several studies showed significant upregulation of IL-17 in tissue, serum, and saliva samples of OLP patients compared with healthy controls. 2,9,11,15,16,23,32,44,78,79,82,[88][89][90][91] Considering T-cell-mediated immune response in pathogenesis of OLP, presence of IL-17 and its regulatory role in OLP is not surprising. It participates in the pathogenesis of OLP through the following mechanisms: (I) reinforcement of T lymphocyte reactions and production of inflammatory mediators such as IL-6, IL-8, and IL-1B, 15,78 (II) regulation of production of matrix metalloproteinase-9 (that breaks type IV collagen leading to impairment of the basement membrane and apoptosis of keratinocytes), 92,93 (III) reduction in diversity of oral bacteria (providing an opportunity for opportunistic pathogens to stimulate the innate and acquired immune system and lead to disease flare-up), 88 (IV) and increased hypersensitivity reactions (through degranulation of mast cells).89 Th17 cells are imperative to coordinate the immune responses elicited by extracellular bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the presence of glaring evidence for lncRNA playing a critical role in the biological processes of human diseases, very few efforts have been made to identify their association with gingivobuccal cancer and assess their prognostic (2,5) . Furthermore the interest in the identification of lncRNA signatures in Gingivobuccal Squamous Cell Carcinoma (GBSCC) stems from the idea of identification of non-invasive biomarkers present in the saliva for early detection of oral cancer (6,7) .…”
Section: Introductionmentioning
confidence: 99%